The Effect of Green Bond Issuance on the Cost of Capital of Stated Owned Banks in Indonesia - Toni Kurniawan; Asep Darmansyah (Green Publisher Indonesia, 2026)
This study examines the impact of green bond issuance on capital costs in Indonesian state-owned banks, focusing on whether green bonds reduce the cost of debt (CoD), cost of equity (CoE), and weighted average cost of capital (WACC) for the issuing bank. This study uses PT Bank Negara Indonesia (Persero) Tbk (BNI) as the treated firm and PT Bank Tabungan Negara (Persero) Tbk (BTN) as the control firm, employing a Difference-in-Differences (DiD) methodology. The analysis is based on 16 quarters of data, comprising 8 quarters prior to and 8 quarters following BNI’s green bond issuance in 2022, covering the period from 2020Q2 to 2024Q2. The empirical findings indicate that the issuance of green bonds does not significantly lower BNI’s CoD, CoE, or WACC. The treatment effect on CoD is positive and not significant, indicating a lack of debt-pricing advantage. The treatment effect on CoE is negative but not significant, suggesting no substantial change in equity investors’ required returns. Additionally, the treatment effect on WACC is slightly positive and statistically not significant. The findings indicate that the Indonesian financial market has not incorporated the sustainability attributes of green bonds into the capital costs of issuers. Factors including the nascent state of Indonesia’s green finance ecosystem, limited involvement from global ESG-focused investors, transitional issuance expenses, and volatility associated with COVID-19 may contribute to these outcomes. This study adds to the existing literature by presenting empirical evidence from an emerging market. It points out the necessity for enhanced disclosure, increased investor engagement.